The Influence of Trade in Services, Inflation, and Foreign Direct Investment on the Sharia Stock Index: A Case Study in Indonesia and Malaysia - Deris Lazuardi; Binti Nur Asiyah (El-Barka Journal of Islamic Economics and Business, 2025)
Abstract: Fluctuations in the prices of sharia-compliant stocks in the capital market are statistically reflected by the sharia stock index. The objective of this study is to analyze the effect of trade in services, inflation, and foreign direct investment (FDI) on the sharia stock index in Indonesia and Malaysia during the period 2011-2023. The researcher in this study used a quantitative method and the data source used was secondary data. The results of the study indicate that, partially, the service trade (trade in services) variable has a positive and significant effect on the sharia stock index, but partially, the inflation and foreign direct investment variables do not have an effect and are not significant on the sharia stock index. Meanwhile, simultaneously, the variables of services trade, inflation, and foreign direct investment have a positive and significant effect on the sharia stock index. The adj. R² value is 89%, meaning that the variables of services trade, inflation, and foreign direct investment can explain 89% of the sharia stock index, and all variables have a very good influence, as the R-squared (R2) value is 91%.